ОЦІНЮВАННЯ ШВИДКОСТІ ВЕКТОРНО-КЕРОВАНИХ АСИНХРОННИХ ДВИГУНІВ НА ОСНОВІ СПОСТЕРІГАЧА - Пересада, С.М.; Ніконенко, Є.О.; Ковбаса, С.М.; Родькін, Д.І.; Кіселичник, О.І. (Інститут електродинаміки НАН України, Київ, 2022)
A speed observer for field-oriented controlled induction drives is presented. The proposed solution exploits the concept of the classic full-order flux observer which is adaptive to the rotor resistance variations. Due to the structural similarity of the rotor speed and active rotor resistance in motor model, the speed observer can be designed using similar structure. The observer guarantees local asymptotic estimation of the rotor fluxes, stator currents and rotor speed in all operating conditions, excluding DC stator excitation. The stability properties of the observer are studied using Lyapunov’s second method. It is experimentally shown that the observer provides an acceptable dynamics of the speed estimation if speed is slowly varying. The proposed observer is suitable for the applications with medium requirements for speed regulation performance. References 13, figures 5.